Sustainable 3D printing with recycled materials: a review - Lodha, Shivani; Song, Bo; Park, Sang-In; Choi, Hae-Jin; Lee, Sang Won; Park, Hyung Wook; Choi, Seung-Kyum (Journal of mechanical science and technology, 2023)
Combining recycling and additive manufacturing (AM) can bring significant environmental and economic advantages. Using recycled materials can help reduce waste and the need for virgin materials, which can be resource-intensive to extract and process. Recycling is also more energy-efficient than extracting and processing virgin materials. This paper reviews and discusses the current trends and limitations of using recycled materials for AM, an essential step toward a more sustainable manufacturing process. Specifically, this paper reviews the research on waste materials transformed into resins for stereolithography (SLA), digital light projection (DLP) printers, filaments for fused deposition modeling (FDM), as well as metal powders for selective laser melting (SLM) and selective laser sintering (SLS) printing processes. The goal is to provide an overview of the recycled materials used in AM, their recycling methods, and the mechanical and thermal properties of the resulting materials and manufactured parts. The paper also discusses potential improvements in the process and areas for future research.